Aural stimulation with capsaicin prevented pneumonia in dementia patients. Issue 1 (February 2020) - Jinnouchi, Osamu; Ohnishi, Hiroki; Kondo, Eiji; Kawata, Ikuji; Bando, Hiroyasu; Okamoto, Hidehiko; Azuma, Takahiro; Sato, Go; Kitamura, Yoshiaki; Abe, Koji; Takeda, Noriaki
Abstract: Objective: In the present study, we examined the effects of daily application of capsaicin ointment to the external auditory canal for 6 months on the development of pneumonia in elderly dementia patients at high risk of aspiration. Methods: Twenty-nine oldest-old bedridden dementia inpatients at high risk of aspiration were enrolled in the present study. Ointment containing 0.025% capsaicin was applied to each external auditory canal with a cotton swab alternatively once a day for 6 months. Results: The incidence of pneumonia during the 6 months before the intervention was 1.80 ± 0.37 in these patients. However, this incidence significantly decreased to 0.40 ± 0.29 (p < 0.01) during the 6 months of the alternative application of capsaicin ointment to each auditory canal. No adverse effect such as otalgia was observed. Conclusion: These findings suggest that daily long-term aural stimulation with capsaicin ointment enhanced the cough reflex via Arnold's ear-cough reflex as a glottis protective measure, resulting in the reduction of incidence of pneumonia in elderly dementia patients at high risk of aspiration. The daily aural stimulation with capsaicin ointment may be a safe and promising intervention to prevent aspiration pneumonia in elderly people, especially those who cannot undergo swallowing exercise.